Bilateral bronchial stent deployment for palliative treatment of a compressive intrathoracic mass in a cat. Issue 1 (February 2018) - Borgeat, Kieran; Simpson, Kerry; Reese, David; Wilson, Helen; Potter, Joanna; Ogden, Daniel
Case summary: Bronchial stents may be useful to relieve clinical signs of extraluminal compression. Herein we describe a case which, to our knowledge, is the first cat where bilateral bronchial stents have been used clinically. Respiratory signs of principal bronchial compression were alleviated after the stent procedure. Minor complications occurred, specifically: severe hypoxia during stent deployment; a transient, self-limiting postoperative pneumothorax possibly associated with ventilation-induced lung injury; bronchopneumonia (possibly pre-existing); and transient worsening of cough postoperatively. Stents were well- tolerated long- term. The cat was euthanased at 44 weeks post-stent procedure, owing to clinical signs of regurgitation, seemingly related to oesophageal dysfunction associated with tumour invasion. Relevance and novel information: In this case, it appeared that bronchial stents were feasible and the procedure was associated with long-term improvement in respiratory signs related to extraluminal bronchial compression.